Preparation method and application of Zhundong coal-based hard carbon material

CN123002820APending Publication Date: 2026-10-30XINJIANG INST OF ENG
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611445277.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-17
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]本发明的目的是提供一种准东煤基硬碳材料的制备方法,该方法可高效除去准东煤中的有机钠,有效解决了目前制备硬碳材料时除杂不彻底和湿法工艺污染严重的问题;本发明同时提供了准东煤基硬碳材料的应用

Benefits of technology

(1)本发明利用醋酸铵与PVC在机械混合和梯级热处理过程中的多阶段协同作用,实现了对准东煤中金属杂质的脱除。机械混合阶段,在高能球磨的强剪切作用下,醋酸铵与煤大分子骨架上键合有机钠发生机械化学复分解反应,将难以脱除的骨架结合态有机钠解离为高度分散游离Na+,便于后续去除;此外,球磨促使PVC长链断裂为短链碎片,并且局部瞬时高温促使少量醋酸铵预分解产生NH3,从而弱化PVC分子C-Cl键,有利于提升后续梯级热处理低温阶段HCl释放速率与释放总量;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123002820A_ABST
    Figure CN123002820A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of sodium ion batteries, and particularly relates to a preparation method and application of a quasi-dong coal-based hard carbon material. Quasi-dong raw coal is crushed, ground, and sieved to obtain coal powder, which is mixed with ammonium acetate, polyvinyl chloride powder and N-methyl pyrrolidone, ball-milled to obtain a mixed powder, and subjected to gradient heat treatment and cooling to obtain the quasi-dong coal-based hard carbon material. The application adopts a full dry impurity removal process, and does not need water washing or acid washing in the whole process, so that no salt-containing acidic wastewater is generated, and the problems of high energy consumption and secondary pollution of the traditional wet process are avoided. The preparation process is simple and easy to operate, and the prepared quasi-dong coal-based hard carbon material has excellent performance when used as a negative electrode of a sodium ion battery, and has great significance for high-value utilization of quasi-dong coal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sodium-ion battery technology, specifically relating to a preparation method and application of a Zhundong coal-based hard carbon material. Background Technology

[0002] Sodium-ion batteries are considered ideal electrochemical energy storage devices for large-scale energy storage and low-speed electric vehicles due to their abundant raw material reserves and low cost. Hard carbon materials, with their disordered carbon layer structure, large interlayer spacing, and abundant porosity, are currently the most promising anode materials for sodium-ion batteries for industrialization. Zhundong coal, with its rich aromatic carbon structure and high carbon content, is an ideal precursor for preparing low-cost hard carbon materials. However, Zhundong coal is a typical high-alkali coal, and its ash is rich in alkali metals such as sodium, calcium, and magnesium, as well as alkaline earth metal impurities. Directly carbonizing it to prepare hard carbon materials has significant drawbacks: First, during the high-temperature carbonization process, oxides formed by metals such as sodium and calcium will block the micropores of hard carbon, reducing the specific surface area of ​​the material and thus significantly reducing the active sites for sodium storage; Second, alkaline earth metals at high temperatures will catalyze the orderly stacking of carbon layers, destroying the amorphous structure of hard carbon, leading to a significant decrease in sodium storage capacity and initial coulombic efficiency.

[0003] To address the aforementioned issues, existing technologies have proposed wet purification processes such as water washing and acid washing. Chinese patent CN122532234A discloses a coal-based composite hard carbon material and its preparation method and application. The preparation method includes Fenton oxidation activation treatment, acid washing for purification, graphene oxide quantum dot-assisted granulation, asphalt coating, and carbonization. However, this type of method can only remove soluble inorganic sodium salts, and its removal efficiency for organic sodium bound to carboxyl and phenolic hydroxyl groups in coal macromolecules is extremely low. Furthermore, wet processes generate large amounts of acidic wastewater containing salt, and subsequent treatment procedures are complex, resulting in high production costs and significant environmental pressure. Chinese patent CN118637595A discloses a coal-based hard carbon anode material and its preparation method, which involves secondary deashing of the coal-based material followed by carbonization to obtain the coal-based hard carbon anode material. However, this patent uses strong acidic and strong alkaline solutions during the preparation process, which can harm the environment. Moreover, the preparation process is complex and cumbersome, making it unsuitable for industrial application. Summary of the Invention

[0004] The purpose of this invention is to provide a method for preparing Zhundong coal-based hard carbon materials. This method can efficiently remove organic sodium from Zhundong coal, effectively solving the problems of incomplete impurity removal and serious pollution from wet processes in the current preparation of hard carbon materials. This invention also provides applications of Zhundong coal-based hard carbon materials.

[0005] The preparation method of the Zhundong coal-based hard carbon material of the present invention includes the following steps: (1) The raw coal from Zhundong is crushed, ground, and sieved to obtain coal powder. The coal powder is mixed with ammonium acetate, polyvinyl chloride (PVC) powder, and N-methylpyrrolidone, and then ball-milled to obtain mixed powder. (2) The mixed powder was subjected to a stepwise heat treatment and then cooled to obtain Zhundong coal-based hard carbon material.

[0006] In step (1), the sieve mesh size is 50 to 200; the degree of polymerization of PVC powder is 800 to 1500.

[0007] In step (1), the mass of ammonium acetate is 10-40% of the mass of coal powder.

[0008] In step (1), the mass of polyvinyl chloride powder is 5 to 30% of the mass of coal powder.

[0009] In step (1), the mass of N-methylpyrrolidone is 10-30% of the mass of coal powder.

[0010] In step (1), the ball mill rotation speed is 300-600 r / min.

[0011] The ball milling time in step (1) is 2 to 12 hours.

[0012] In step (2), the cascade heat treatment and cooling are carried out under the protection of an inert gas, which is either argon or nitrogen, and the flow rate of the inert gas is 50-300 mL / min.

[0013] In step (2), the stepped heat treatment is a two-stage continuous heat treatment, including a low temperature stage and a high temperature stage (high temperature carbonization stage); the low temperature stage is to raise the temperature from room temperature to 300-450℃ and hold it for 2-6 hours, with a heating rate of 2-5℃ / min; the high temperature stage is to raise the temperature to 1100-1600℃ and hold it for 2-4 hours after the low temperature stage, with a heating rate of 2-5℃ / min.

[0014] The application of the Zhundong coal-based hard carbon material described in this invention is in sodium-ion batteries.

[0015] The beneficial effects of this invention are as follows: (1) This invention utilizes the multi-stage synergistic effect of ammonium acetate and PVC during mechanical mixing and stepped heat treatment to remove metallic impurities from Zhundong coal. In the mechanical mixing stage, under the strong shearing action of high-energy ball milling, ammonium acetate undergoes a mechanochemical metathesis reaction with the organic sodium bound to the coal macromolecular skeleton, dissociating the difficult-to-remove skeleton-bound organic sodium into highly dispersed free Na. + This facilitates subsequent removal; in addition, ball milling causes the long chains of PVC to break into short chain fragments, and the local instantaneous high temperature causes a small amount of ammonium acetate to pre-decompose to produce NH3, thereby weakening the C-Cl bond of PVC molecules, which is beneficial to improving the HCl release rate and total amount released in the low-temperature stage of subsequent step heat treatment. During the low-temperature stage of the cascade heat treatment, PVC undergoes vigorous dechlorination to generate highly reactive HCl gas, which reacts with highly alkaline substances (alkali metal impurities and alkaline earth metal impurities) to produce nanoscale metal chlorides such as NaCl, KCl, and MgCl2. The NH3 produced by the decomposition of ammonium acetate reacts with the HCl released from PVC to generate NH4Cl in situ. NH4Cl serves as a temporary storage and slow-release medium for HCl, preventing HCl from being rapidly diluted and lost by the inert gas flow. Further heating can decompose and release HCl, prolonging the residence time of HCl in the pores of coal particles and promoting the diffusion of HCl into the particle interior to react with accessible impurities. At the same time, NH4Cl itself can also act as an in-situ chlorinating agent, reacting with some metal oxides to generate metal chlorides. During the high-temperature stage of the cascade heat treatment, the nanoscale metal chloride particles or the gas produced by the gasification of metal chlorides can be discharged under continuous inert gas flow, thereby achieving the removal of metal impurities.

[0016] (2) The NH3 produced by the decomposition of ammonium acetate and the HCl gas produced by the decomposition of PVC continue to escape during the low-temperature stage of the stepped heat treatment, forming initial micropores on the carbon matrix in Zhundong coal. During the high-temperature carbonization stage, the carbon layer rearrangement causes the micropores to close, forming a rich closed-pore structure. At the same time, the removal of metal impurities effectively inhibits the catalytic graphitization effect of metal impurities at high temperature, promotes the carbon skeleton to maintain an amorphous hard carbon structure, and provides abundant storage sites and fast transport channels for sodium ions, so that the Zhundong coal-based hard carbon material has high specific capacity (reversible capacity) and excellent first coulombic efficiency.

[0017] (3) The present invention adopts a dry method for removing impurities. No water washing or acid washing is required in the whole process, and no salt-containing acidic wastewater is generated. It avoids the high energy consumption and secondary pollution problems of traditional wet process. The preparation process is simple and easy to operate. The prepared Zhundong coal-based hard carbon material has excellent performance when used as a negative electrode of sodium-ion battery. It is of great significance for the high-value utilization of Zhundong coal. Attached Figure Description

[0018] Figure 1 The image shows the XRD pattern of the Zhundong coal-based hard carbon material in Example 1.

[0019] Figure 2 This is a charge-discharge curve of the sodium-ion battery in Example 1.

[0020] Figure 3 This is a charge-discharge curve of the sodium-ion battery in Example 2.

[0021] Figure 4 This is a charge-discharge curve of the sodium-ion battery in Example 3.

[0022] Figure 5 This is a charge-discharge curve of the sodium-ion battery in Example 4.

[0023] Figure 6 The image shows the XRD pattern of the Zhundong coal-based hard carbon material in Comparative Example 1.

[0024] Figure 7 The above is a charge-discharge curve of the sodium-ion battery in Comparative Example 1.

[0025] Figure 8 The image shows the XRD pattern of the Zhundong coal-based hard carbon material in Comparative Example 2.

[0026] Figure 9 The above is a charge-discharge curve of the sodium-ion battery in Comparative Example 2. Detailed Implementation

[0027] The present invention will be further described below with reference to embodiments.

[0028] Example 1 Preparation of Zhundong coal-based hard carbon materials: (1) Crush and grind the raw coal from Zhundong and pass it through a 200-mesh sieve to obtain coal powder; weigh 100g of coal powder, 20g of ammonium acetate, 20g of PVC powder (polymerization degree of 800) and 20g of N-methylpyrrolidone and place them in a ball mill jar and mix them. Under the protection of high-purity nitrogen, the mixture is ball-milled at a speed of 450r / min for 2h to obtain mixed powder. (2) The mixed powder from step (1) was added to a tube furnace and heated from room temperature to 350°C at a heating rate of 2°C / min under a high-purity argon carrier gas atmosphere (flow rate 200 mL / min) for 5 hours. Then, the temperature was increased to 1100°C at a heating rate of 5°C / min and held for 2 hours for high-temperature carbonization. After carbonization, the furnace was cooled to room temperature under an argon atmosphere to obtain a black solid product, namely Zhundong coal-based hard carbon material. The XRD pattern of Zhundong coal-based hard carbon material is shown in the figure. Figure 1 .

[0029] Applications of Zhundong coal-based hard carbon materials: Zhundong coal-based hard carbon material was used as the negative electrode material for sodium-ion batteries. It was mixed with conductive carbon black and polyvinylidene fluoride (PVDF) in a beaker, with the mass ratio of Zhundong coal-based hard carbon material, conductive carbon black and PVDF being 8:1:1. N-methylpyrrolidone was then added dropwise and stirred for 12 hours to obtain a black slurry. The black slurry was evenly coated on the surface of copper foil and placed in a vacuum drying oven at 80°C for 12 hours. Finally, the copper foil was cut to obtain an electrode sheet with a diameter of 1.5 cm. Using the aforementioned electrode sheet as the negative electrode, sodium foil as the counter electrode, and NaPF6 solution (1M concentration, a mixture of ethylene carbonate and diethyl carbonate in a 1:1 volume ratio) as the electrolyte, a coin cell was assembled. Charge-discharge tests were performed on the sodium-ion battery using the Blue Battery Testing System. The charge-discharge curves of the sodium-ion battery are shown below.Figure 2 The sodium-ion battery has a reversible capacity of 338 mAh / g at 50 mA / g and an initial coulombic efficiency of 90%.

[0030] Example 2 Preparation of Zhundong coal-based hard carbon materials: (1) Crush and grind the raw coal from Zhundong and pass it through a 200-mesh sieve to obtain coal powder; weigh 100g of coal powder, 25g of ammonium acetate, 5g of PVC powder (polymerization degree of 800) and 20g of N-methylpyrrolidone and place them in a ball mill jar and mix them. Under the protection of high-purity nitrogen, the mixture is ball-milled at a speed of 450r / min for 12h to obtain mixed powder. (2) The mixed powder from step (1) is added to a tube furnace and heated from room temperature to 350°C at a heating rate of 2°C / min under a high-purity argon carrier gas atmosphere (flow rate 200 mL / min) for 5 hours. Then, the temperature is further increased to 1300°C at a heating rate of 5°C / min and held for 2 hours for high-temperature carbonization. After carbonization, the furnace is cooled to room temperature under an argon atmosphere to obtain a black solid product, namely Zhundong coal-based hard carbon material.

[0031] Applications of Zhundong coal-based hard carbon materials: The preparation methods for the electrode sheet and sodium-ion battery are the same as in Example 1; the sodium-ion battery was tested for charge and discharge using a Blue Battery testing system, and the charge and discharge curves of the sodium-ion battery are shown in [Figure 1]. Figure 3 The sodium-ion battery has a reversible capacity of 373 mAh / g at 50 mA / g and a first-time coulombic efficiency of 79.8%.

[0032] Example 3 Preparation of Zhundong coal-based hard carbon materials: (1) Crush and grind the raw coal from Zhundong and pass it through a 50-mesh sieve to obtain coal powder; weigh 100g of coal powder, 40g of ammonium acetate, 10g of PVC powder (polymerization degree of 800) and 10g of N-methylpyrrolidone and place them in a ball mill jar and mix them. Under the protection of high-purity nitrogen, the mixture is ball-milled at a speed of 600r / min for 6h to obtain mixed powder. (2) The mixed powder from step (1) is added to a tube furnace and heated from room temperature to 300°C at a heating rate of 3°C / min under a high-purity argon carrier gas atmosphere (flow rate 300 mL / min) for 6 hours. Then, the temperature is further increased to 1400°C at a heating rate of 2°C / min and held for 4 hours for high-temperature carbonization. After carbonization, the furnace is cooled to room temperature under an argon atmosphere to obtain a black solid product, namely Zhundong coal-based hard carbon material.

[0033] Applications of Zhundong coal-based hard carbon materials: The preparation methods for the electrode sheet and sodium-ion battery are the same as in Example 1; the sodium-ion battery was tested for charge and discharge using a Blue Battery testing system, and the charge and discharge curves of the sodium-ion battery are shown in [Figure 1]. Figure 4 The sodium-ion battery has a reversible capacity of 321 mAh / g at 50 mA / g and a first-time coulombic efficiency of 75.2%.

[0034] Example 4 Preparation of Zhundong coal-based hard carbon materials: (1) Crush and grind the raw coal from Zhundong and pass it through a 100-mesh sieve to obtain coal powder; weigh 100g of coal powder, 10g of ammonium acetate, 30g of PVC powder (polymerization degree of 800) and 30g of N-methylpyrrolidone and place them in a ball mill jar and mix them. Under the protection of high-purity nitrogen, the mixture is ball-milled at a speed of 300r / min for 2h to obtain mixed powder. (2) The mixed powder from step (1) is added to a tube furnace and heated from room temperature to 450°C at a heating rate of 5°C / min under a high-purity nitrogen carrier gas atmosphere (flow rate 50 mL / min) for 2 hours. Then, the temperature is further increased to 1600°C at a heating rate of 4°C / min and held for 3 hours for high-temperature carbonization. After carbonization, the furnace is cooled to room temperature under a nitrogen atmosphere to obtain a black solid product, namely Zhundong coal-based hard carbon material.

[0035] Applications of Zhundong coal-based hard carbon materials: The preparation methods for the electrode sheet and sodium-ion battery are the same as in Example 1; the sodium-ion battery was tested for charge and discharge using a Blue Battery testing system, and the charge and discharge curves of the sodium-ion battery are shown in [Figure 1]. Figure 5 The sodium-ion battery has a reversible capacity of 321.5 mAh / g at 50 mA / g and a first-time coulombic efficiency of 85%.

[0036] Comparative Example 1 Preparation of Zhundong coal-based hard carbon materials: Without adding PVC powder, other operations were the same as in Example 1 to obtain Zhundong coal-based hard carbon material; the XRD pattern of the Zhundong coal-based hard carbon material is shown below. Figure 6 Impurity removal was incomplete, and impurity peaks appeared.

[0037] Applications of Zhundong coal-based hard carbon materials: The preparation methods for the electrode sheet and sodium-ion battery are the same as in Example 1; the sodium-ion battery was tested for charge and discharge using a Blue Battery testing system, and the charge and discharge curves of the sodium-ion battery are shown in [Figure 1]. Figure 7 The sodium-ion battery has a reversible capacity of 294 mAh / g at 50 mA / g and an initial coulombic efficiency of 65.6%.

[0038] Comparative Example 2 Preparation of Zhundong coal-based hard carbon materials: Without adding ammonium acetate, other operations were the same as in Example 1 to obtain Zhundong coal-based hard carbon material; the XRD pattern of the Zhundong coal-based hard carbon material is shown below. Figure 8 Impurity removal was incomplete, and impurity peaks appeared.

[0039] Applications of Zhundong coal-based hard carbon materials: The preparation methods for the electrode sheet and sodium-ion battery are the same as in Example 1; the sodium-ion battery was tested for charge and discharge using a Blue Battery testing system, and the charge and discharge curves of the sodium-ion battery are shown in [Figure 1]. Figure 9 The sodium-ion battery has a reversible capacity of 215 mAh / g at 50 mA / g and an initial coulombic efficiency of 67.8%.

Claims

1. A method for preparing a Zhundong coal-based hard carbon material, characterized in that... Includes the following steps: (1) The raw coal from Zhundong is crushed, ground, and sieved to obtain coal powder. The coal powder is mixed with ammonium acetate, polyvinyl chloride powder, and N-methylpyrrolidone, and then ball-milled to obtain mixed powder. (2) The mixed powder was subjected to a stepwise heat treatment and then cooled to obtain Zhundong coal-based hard carbon material.

2. The method for preparing Zhundong coal-based hard carbon material according to claim 1, characterized in that... In step (1), the sieve mesh size is 50 to 200 mesh.

3. The method for preparing Zhundong coal-based hard carbon material according to claim 1, characterized in that... In step (1), the mass of ammonium acetate is 10-40% of the mass of coal powder.

4. The method for preparing Zhundong coal-based hard carbon material according to claim 1, characterized in that... In step (1), the mass of polyvinyl chloride powder is 5 to 30% of the mass of coal powder.

5. The method for preparing Zhundong coal-based hard carbon material according to claim 1, characterized in that... In step (1), the mass of N-methylpyrrolidone is 10-30% of the mass of coal powder.

6. The method for preparing Zhundong coal-based hard carbon material according to claim 1, characterized in that... In step (1), the ball mill rotation speed is 300-600 r / min.

7. The method for preparing Zhundong coal-based hard carbon material according to claim 1, characterized in that... The ball milling time in step (1) is 2 to 12 hours.

8. The method for preparing Zhundong coal-based hard carbon material according to claim 1, characterized in that... In step (2), the cascade heat treatment and cooling are carried out under the protection of an inert gas, which is either argon or nitrogen, and the flow rate of the inert gas is 50-300 mL / min.

9. The method for preparing Zhundong coal-based hard carbon material according to claim 1, characterized in that... In step (2), the stepped heat treatment is a two-stage continuous heat treatment, including a low temperature stage and a high temperature stage. The low temperature stage is to raise the temperature from room temperature to 300-450℃ and hold it for 2-6 hours, with a heating rate of 2-5℃ / min. The high temperature stage is to raise the temperature to 1100-1600℃ and hold it for 2-4 hours after the low temperature stage, with a heating rate of 2-5℃ / min.

10. An application of a Zhundong coal-based hard carbon material prepared by the preparation method of Zhundong coal-based hard carbon material according to any one of claims 1-9, characterized in that... Applications in sodium-ion batteries.

Citation Information

Patent Citations

  • Coal-based hard carbon negative electrode material and preparation method thereof

    CN118637595A

  • Coal-based composite hard carbon material as well as preparation method and application thereof

    CN122532234A